Mechanical, thermal and morphological properties of glutaraldehyde crosslinked bovine pericardium followed by glutamic acid treatment - Goissis,Gilberto (2009)
Major problems with valve bioprostheses are associated with progressive structural deterioration and calcification, directly associated with the use of glutaraldehyde (GA). This work describes the effects of GA processing and borate/glutamic acid buffer treatment on the mechanical, thermal and morphological properties of 0.5% GA crosslinked bovine pericardium (BP). The results showed that while the treatment of 0.5% GA crosslinked BP with borate/glutamic acid significantly improves the mechanical properties, it had no visible effect on surface morphology. Better surface preservation was only achieved for BP pre-treated with a lower GA concentration followed by the conventional treatment (0.5% GA). Improvements in mechanical properties probably arises from structural changes probably involving the depolymerization of polymeric GA crosslinks and an increase electrostatic interaction due to covalent binding of glutamic acid to free carbonyl groups (Schiff base).The results indicate that the treatment GA crosslinked BP with borate/glutamic acid buffer may be an attractive procedure for the manufacture of heart valve bioprostheses.